Canadian Physical Education and Kinesiology Unit Mission Statements: Who is Playing by the Rules of the Game?. (2nd October 2018) - Lorusso, Jenna R.; Morrison, Hayley J.; Johnson, Ashley M.
ABSTRACT: A mission statement can be understood as a declaration about the basic purpose of an organization. Given the low-consensus discipline of physical education/kinesiology (PEKN), and the limited research on its academic units' mission statements, the purpose of this research was to investigate the content of these statements and what discourses they assert. To do so, the mission statements of units granting PEKN degrees in Canada were collected by accessing each university's institutional webpage. Data were analyzed via the hermeneutic circle to inductively identify themes, and through Tinning's (1997) theory of performance and participation discourses in human movement to deductively analyze discourses. Results revealed that only half of Canadian PEKN units had mission statements. Of those units with mission statements, the content of those statements (i.e., the unit's stated products, services, and goals; community(ies) served; approach(es) taken; and standards of success) were more similar in their market strategies than in their disciplinary agenda or discourse. Perhaps it is time to shift from battling over participation and performance discourses to a new set of "p" discourses, specifically figuring out how to adopt a pragmatic and principled discourse in PEKN. Units should have pragmatic mission statements that communicate effectively to those inside and outside the university for survival, but should also be principled in that those mission statements must not simply offer what the university or potential students want at a specific moment, but also what will make an important contribution to society in the long-term.